STRATEGI KOMUNIKASI PEMERINTAH KOTA DEPOK MENYAMBUT NEW NORMAL - Tjahyo Rawinarno Tjahyo Rawinarno; Suhud Alynudin Suhud Alynudin; Najwa Shafira Najwa Shafira (LPPM STIA Banten, 2021)
Background of this research is started when Depok City, Java Province, become first city that infected by Corona Virus Desease in Indonesia, October 2021 Depok become orange zone, meaning Depok Government succed decrease the spread of Covid-19. Counting on one year of pandemic, some of Communication strategy been implemented, divided as four phases: Outbreak, during Limitation Scale, New adaptation, and Behaviour Changing. Concept that be used as guidance are about adjustment of bureaucracy from Prasojo (2020). Research methode that used is descriptive qualitative. Approaching by literature study from government and other resources that relevant. The result is Government of Depok City had capability to implement those five component. Government needs to strengthen the application of the related Depok Covid-19 Information Center (PICODEP) so that reconciliation data can be easily clarified, so that it can be the basis for policy formulation.